Preserved caudate function in young-onset patients with Parkinson’s disease: a dual-tracer PET imaging study - Yu-jie Yang; Jing-jie Ge; Feng-tao Liu; Zhen-yang Liu; Jue Zhao; Jian-jun Wu; Yilong Ma; Chuan-tao Zuo; Jian Wang (Therapeutic Advances in Neurological Disorders, 2019)
Parkinson’s disease (PD) is a highly heterogeneous clinical entity. Patients with young-onset PD (YOPD) show some characteristic manifestations to late-onset PD (LOPD). The current study aimed to investigate the cerebral dopaminergic and metabolic characteristics in YOPD with positron emission tomography (PET) imaging. In our study, 103 subjects (42 YOPD and 61 LOPD patients) accepted both 11 C-N-2-carbomethoxy-3-(4-fluorophenyl)-tropane ( 11 C-CFT) and 18 F-fluorodeoxyglucose ( 18 F-FDG) cerebral PET imaging. Sixty-two patients out of 103 patients in our study completed the cognition tests. In this limited subsection, YOPD patients performed better in cognitive functioning than LOPD patients of similar disease duration. In 11 C-CFT imaging, dopamine transporter binding in caudate was relatively spared in YOPD compared with lesions in putamen. In 18 F-FDG PET, YOPD patients showed increased metabolism in basal ganglia relative to the healthy controls. When compared with LOPD patients, YOPD patients exhibited hypermetabolism in caudate and hypometabolism in putamen. Furthermore, the regional metabolic values in caudate correlated positively and moderately with the dopaminergic binding deficiency in caudate. The findings of this imaging study might offer new perspectives in understanding the characteristic manifestations in YOPD in light of better-preserved cognition function.